Upaya Meningkatkan Kemampuan Komunikasi Matematis Siswa dengan Konteks Pandemi Covid-19 di MAN 1 Madina - Eline Yanty Putri Nasution; Purnama Hayati (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
This study was a classroom action research that contain two cycles with pomoting the improvement of student’s mathematical communication ability. This study was applied in Madrasah Aliyah Negeri (MAN) 1 Mandailing Natal (Madina) Plus Keterampilan in the XI MIA grade year 2020/2021 during the covid-19 pandemic. The object of this study was 35 students of XI MIA 2 grade from 165 students of XI MIA grade as the research population. The subject of this study was student’s mathematical communication ability. This study used the student’s mathematical communication ability test and interview instruments that had been carried out the instruments feasibility test. Based on the analysis of the data, we found: (1) the average of student’s mathematical communication ability test increase from 77 at cycle I to 91 at cycle II; (2) the number of students who have mathematical communication ability increase from 16 (46%) students at cycle I to 27 (77%) students at cycle II. The conclusion of this study is covid-19 pandemic context can improve the student’s mathematical communication ability.